A novel patient with White–Sutton syndrome refines the mutational and clinical repertoire of the POGZ‐related phenotype and suggests further observations. Issue 7 (2nd May 2020) - Pascolini, Giulia; Agolini, Emanuele; Fleischer, Nicole; Gulotta, Elisa; Cesario, Claudia; D'Elia, Gemma; Novelli, Antonio; Majore, Silvia; Grammatico, Paola
Abstract: A rare developmental delay (DD)/intellectual disability (ID) syndrome with craniofacial dysmorphisms and autistic features, termed White–Sutton syndrome (WHSUS, MIM#614787), has been recently described, identifying truncating mutations in the chromatin regulator POGZ (KIAA0461, MIM#614787). We describe a further WHSUS patient harboring a novel nonsense de novo POGZ variant, which afflicts a protein domain with transposase activity less frequently impacted by mutational events (DDE domain). This patient displays additional physical and behavioral features, these latter mimicking Smith–Magenis syndrome (SMS, MIM#182290). Considering sleep–wake cycle anomalies and abnormal behavior manifested by this boy, we reinforced the clinical resemblance between WHSUS and SMS, being both chromatinopathies. In addition, using the DeepGestalt technology, we identified a different facial overlap between WHSUS patients with mutations in the DDE domain (Group 1) and individuals harboring variants in other protein domains/regions (Group 2). This report further delineates the clinical and molecular repertoire of the POGZ ‐related phenotype, adding a novel patient with uncommon clinical and behavioral features and provides the first computer‐aided facial study of WHSUS patients.